Fruit and Seed Quality as Influenced by Differential Emasculation Time and Crossing Period in Hybrid Brinjal (Solanum melongena L.) - PRITPAL SINGH; GEETA BASSI; AMANDEEP KAUR; J.C. THAKUR (Seed Research, 2026)
The parents of two hybrids Brinjal Hybrid-1 (BH-1) and Brinjal Hybrid-2 (BH-2) of brinjal (Solanum melongena L.) i.e. Jamuni Gola (female parent of BH-1), Punjab Neelam (female parent of BH-2) and Punjab Barsati (male parent of both), were subjected to two emasculation times i.e. emasculation time-1 (9.00-11.00 A.M.) and emasculation time-2 (3.00-5.00 P.M.) and six crossing periods in the month of September and October, 2003. Duration of each crossing period was of 10 days. Significant differences were observed between emasculation times and crossing periods in both the crosses. Significantly higher fruit set, fruit weight, quantity of seed per unit weight of fruit, 1000-seed weight, germination per cent and seed vigour were registered in the plants emasculated in the afternoon (3.00-5.00 P.M.) than those emasculated in the morning hours. Maximum fruit setting was observed in crossing period-5 (October, 11-20). For all other characters crossing period-3 (September 21-30) was the best in both the crosses.